Hubungan antara Angka Kejadian Acute Kidney Injury dengan Infeksi Saluran Kemih di RSUD Provinsi NTB - JAYADI, AGUNG; Pandu Ishaq Nandana; Maz Isa Ansyori Arsatt; Indah Sapta Wardani (Lombok Medical Journal, 2025)
Acute Kidney Injury (AKI) is a global health problem with high morbidity and mortality rates. The prevalence of AKI in hospitalized patients ranges from 2% to 5% increasing to 67% in intensive care units (ICU). A sudden decrease in kidney function characterizes acute kidney injury and is usually reversible, risk factors include pre-existing kidney disease, such as chronic kidney disease (CKD), and sepsis. The causes of AKI can be categorized into three groups: prerenal, which is caused by reduced blood flow to the kidneys; renal, associated with glomerular or tubular damage; and postrenal, which results from obstruction that disrupts the kidney's filtration system. Uncomplicated urinary tract infections (UTIs) are bacterial infections of the bladder and related structures, which occur frequently, especially in women. UTI can progress to sepsis. A systemic inflammatory response that can cause multi-organ dysfunction or failure, including AKI. Approximately 25% of sepsis cases originate from urogenital tract infections.